2020
DOI: 10.1089/hum.2019.195
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Interleukin-10 Transgene Expression Following Intra-Articular AAV5-IL-10 Administration to Horses

Abstract: Joint trauma leads to post-traumatic inflammation with upregulation of inflammatory cytokines and degradative enzymes. If severe enough, this response can lead to irreversible post-traumatic osteoarthritis. Interleukin-10 (IL-10), a cytokine with potent anti-inflammatory effects, has been shown to have chondroprotective effects. A gene therapy approach using a vector to overexpress IL-10 in the joint represents a feasible method of delivering sustained high doses of IL-10 to post-traumatic joints. We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Some of the experimental procedures described below can be found in more detail in a published paper by Moss et al 21 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the experimental procedures described below can be found in more detail in a published paper by Moss et al 21 …”
Section: Methodsmentioning
confidence: 99%
“…A rAAV‐IL10 viral vector was generated by the University of North Carolina Vector Core as described previously 21 . Briefly, the vector consisted of an equine IL‐10 transgene, flanked by AAV2 inverted terminal repeats (ITRs) and under control of a cytomegalovirus (CMV) promoter (Figure 1) incorporated into the AAV5 viral capsule.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibiting IL-17 signaling in the horse will not be as simple as applying human therapies since the most successful psoriasis treatments use monoclonal antibodies to block IL- 17 receptor activation [21]; these antibodies may not bind the equine IL-17 receptor, may be antigenic in equines, and are likely cost-prohibitive. Local inhibition of IL-17 and/or mTORC1 would be desirable, and could be possible using an adeno-associated viral vector to deliver genes for inhibitory cytokines to reduce inflammation, as demonstrated recently [83], or other genes able to inhibit IL-17 and/or mTORC1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in veterinary medical technologies have enabled gene therapy in horses, and several clinical studies have been reported [4][5][6]. Gene therapy may be technically categorized into gene transfer, gene silencing and gene editing.…”
Section: Introductionmentioning
confidence: 99%